2021
DOI: 10.1108/caer-10-2020-0251
|View full text |Cite
|
Sign up to set email alerts
|

Interactive relationship between non-farm employment and mechanization service expenditure in rural China

Abstract: PurposeThe purpose of this study is to investigate the interactive relationship between non-farm employment and mechanization service expenditure.Design/methodology/approachThe study employs an innovative two-stage probit least squares (2SPLS) model to analyze the survey data collected from 1,148 rural households in China. This model not only simultaneously estimates the impact of non-farm employment on mechanization service expenditure and the impact of mechanization service expenditure on non-farm employment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…The rapid development of agricultural socialized services has given farmers access to lower-cost and higher-level services. By outsourcing services, farmers gain access to the superior resources of service organizations [46], reduce agricultural production costs and weak labor constraints [47,48], and can therefore promote cultivated land quality conservation with optimal allocation. In terms of service provision, agricultural socialized services share the risk of investment in technology or equipment and improve resource utilization by integrating the needs of dispersed farmers, who have the opportunity to obtain better service with lower input [49].…”
Section: Capital Replaces Labormentioning
confidence: 99%
“…The rapid development of agricultural socialized services has given farmers access to lower-cost and higher-level services. By outsourcing services, farmers gain access to the superior resources of service organizations [46], reduce agricultural production costs and weak labor constraints [47,48], and can therefore promote cultivated land quality conservation with optimal allocation. In terms of service provision, agricultural socialized services share the risk of investment in technology or equipment and improve resource utilization by integrating the needs of dispersed farmers, who have the opportunity to obtain better service with lower input [49].…”
Section: Capital Replaces Labormentioning
confidence: 99%
“…Core independent variables: (1) Livestock sales scale, or the number of livestock sold by herders in the current year, in sheep units; (2) non-pastoral employment (NPE), including local non-pastoral work and rural-to-urban migration, and measured by a binary variable that was 1 if any household member was employed in any non-pastoral work, and 0 otherwise. Furthermore, the ratio of the NPE time-of-household labor against the whole year was measured to identify the substitution effect of NPE, since it could more accurately characterize the degree of NPE, and could solve the estimation bias caused by the inconsistency of the time span of NPE [37,38]. The ratio of NPE income to the total household income was used to measure the wealth effect, representing the non-pastoral employability of herders.…”
Section: Variable Definitions and Descriptive Analysismentioning
confidence: 99%
“…Ranis-Fei has also suggested that low labor productivity severely reduces the likelihood of labor migration. Land transfer can concentrate land resources to those who are willing to farm or are capable of farming [ 61 , 62 ], improve the utilization rate of agricultural machinery through continuous scale operation, better apply new technology in the production process, improve agricultural labor productivity and release the surplus labor force in the countryside [ 63 , 64 , 65 ]. Fourth, land transfer promotes the rural labor transfer by weakening the land safeguard function [ 66 , 67 ].…”
Section: Literature Review and Theoretical Mechanismsmentioning
confidence: 99%